2016
DOI: 10.1080/23746149.2016.1228476
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted photoporation: fundamentals, technological advances and applications

Abstract: Laser-assisted photoporation is a promising technique that is receiving increasing attention for the delivery of membrane impermeable nanoscopic substances into living cells. Photoporation is based on the generation of localized transient pores in the cell membrane using continuous or pulsed laser light. Increased membrane permeability can be achieved directly by focused laser light or in combination with sensitizing nanoparticles for higher throughput. Here, we provide a detailed account on the history and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(110 citation statements)
references
References 172 publications
(227 reference statements)
0
104
0
Order By: Relevance
“…The main difficulties are related to the impermeability of the plasma membrane, which, after a billion years of evolutionary defenses, strictly controls the trafficking in and out of the cell. The most popular methods for intracellular delivery are electroporation [6], chemical transfection, and virus-mediated transduction, although novel methods have been considered recently [7,8,9,10]. Among them, local membrane permeabilization through vertical nanopillars or other 3D nanostructures is emerging as a robust approach [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The main difficulties are related to the impermeability of the plasma membrane, which, after a billion years of evolutionary defenses, strictly controls the trafficking in and out of the cell. The most popular methods for intracellular delivery are electroporation [6], chemical transfection, and virus-mediated transduction, although novel methods have been considered recently [7,8,9,10]. Among them, local membrane permeabilization through vertical nanopillars or other 3D nanostructures is emerging as a robust approach [11,12,13,14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Efficient delivery of molecules into cells is needed for applications in the laboratory and the clinic that seek to alter cell behavior using small molecules, proteins, nucleic acids, and other bioactive compounds (Fu et al, 2014;Yang and Hinner, 2015). In addition to methods that rely on active transport mechanisms to enter the cell (e.g., endocytosis), there are a number of biophysical approaches that transiently permeabilize the cell membrane to deliver molecules intracellularly, such as ultrasound (Castle et al, 2013;Lentacker et al, 2014;Liu et al, 2012), electroporation (Kim and Lee, 2017;Yarmush et al, 2014), and photoporation methods (Chakravarty et al, 2010;Clark et al, 2014;Davis et al, 2013;Delcea et al, 2012;Kalies et al, 2014;Kodama et al, 2000;Lukianova-Hleb et al, 2014;Sengupta et al, 2014;Terakawa et al, 2013;Waleed et al, 2013;Wu et al, 2015;Xiong et al, 2016). When using these methods, there is a delicate balance between delivery of molecules and retaining high cell viability, wherein excessive physical stresses can damage the cell irreversibly, resulting in cell death.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is often difficult to optimize physical methods to achieve delivery and maintain cell viability, as excessive physical forces can irreversibly damage the cells and cause cell death. There is a growing interest in laser‐mediated methods, facilitated by a phenomenon known as photoporation to deliver molecules to the cytosol . Our previous studies have shown that when carbon‐black (CB) nanoparticles in suspension with cells and extracellular molecules are irradiated by nanosecond‐pulsed near‐infrared (NIR) laser energy, high molecular delivery and viability can be achieved by photoporation …”
Section: Introductionmentioning
confidence: 99%